Oxide-containing copper microparticles, method for producing same, and method for producing sintered body of copper microparticles
By adding oxides and carboxylic acid coating to the copper particles, the full conductivity of the copper particles is achieved by heating by primary heating, and the problems of complex sintering process and low productivity in the prior art are solved, and efficient low-temperature conductive sintering is achieved.
Patent Information
- Application Number
- CN202411386298.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-08-26
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, copper particles sintering requires two-stage heating or high vacuum conditions, low productivity and complex process, making it difficult to achieve sufficient conductivity at low temperatures.
Using oxide-containing copper particles, Cu64O and Cu2O with a specific mass ratio is heated at a time at normal pressure below 200°C, and carboxylic acid flux is used to promote the reduction of Cu64O, so as to achieve full bonding of copper particles. and conductivity.
Without the need for two-stage heating and additional materials, a sintered body with sufficient conductivity is achieved at a normal pressure below 200°C, which improves productivity and simplifies the process.
Smart Images

Figure CN119259994A_ABST
Abstract
Description
[0001] This application is a divisional application of the following application:
[0002] Invention name: Oxide-containing copper microparticles and a method for producing the same, and a method for producing a sintered body using the oxide-containing copper microparticles.
[0003] International filing date: August 26, 2021.
[0004] International application number: PCT / JP2021 / 031373.
[0005] National application number: 202180031320.1. Technical Field
[0006] The present disclosure relates to oxide-containing copper microparticles, a method for producing the same, and a method for producing a sintered body using the oxide-containing copper microparticles. Background Art
[0007] In recent years, in the manufacture of printed circuit boards, a technology called Print Full Electronics, which directly forms fine wiring using inkjet or printing methods, has attracted attention as a clean technology that does not require conventional exposure and etching and does not emit harmful chemical substances.
[0008] The above-mentioned fine wiring is mainly obtained by heating metal particles to sinter them. From the perspective of heat resistance of the substrate, the metal particles are required to be sintered at a temperature lower than 250-350°C, for example. At present, silver particles that can be sintered at low temperatures are mostly used, but silver particles are expensive and may cause wiring short circuits due to ion migration. As an alternative to silver particles, copper particles that are cheap and highly resistant to ion migration have attracted attention, but copper particles have the problem of being difficult to sinter at low temperatures and have not been put into practical use.
[0009] In contrast, the present inventors have been able to sinter copper particles at temperatures below 200° C. by two-stage heating (Patent Document 1), introduction of a copper complex ink (Patent Document 2), and inclusion of cuprous oxide (Cu 2 O) in copper particles (Patent Document 3).
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2015-214722
[0013] Patent Document 2: Japanese Patent Application Publication No. 2017-1978
[0014] Patent Document 3: International Publication No. 2019 / 106739 Summary of the invention
[0015] Problems to be solved by the invention
[0016] However, Patent Document 1 requires two-stage heating (oxidation treatment and reduction treatment), and Patent Document 2 requires the preparation of additional copper materials (copper complexes) in addition to copper particles (copper powder), both of which require many steps. Patent Document 3 requires sintering under high vacuum, and intermittent processing is required for entering and exiting vacuum equipment, which reduces productivity.
[0017] The present invention has been completed in view of such a situation, and one of its purposes is to provide a copper particle and a method for producing a copper particle and a method for producing a sintered body using the copper particle, wherein the copper particle does not require two-stage heating and additional copper material, and a sintered body showing sufficient conductivity can be obtained by a single heating at a temperature below 200° C. under normal pressure (or a pressure higher than that).
[0018] Solutions for solving problems
[0019] Aspect 1 of the present invention is an oxide-containing copper particle, wherein the oxide-containing copper particle comprises Cu 64 O and Cu2O as required, and is coated with carboxylic acids, wherein Cu 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is 0.5 to 2.0 mass%.
[0020] Aspect 2 of the present invention is the oxide-containing copper microparticles according to aspect 1, wherein Cu2O is 64 The mass ratio of the total mass of O and Cu2O is 0 mass% or more and less than 0.5 mass%.
[0021] Aspect 3 of the present invention is the oxide-containing copper microparticles according to aspect 1, wherein Cu2O is 64 The mass ratio of the total mass of O and Cu2O is 0.5 to 2.0 mass%.
[0022] Scheme 4 of the present invention is a method for producing oxide-containing copper particles, which is a method for producing oxide-containing copper particles as described in any one of Schemes 1 to 3, and the production method includes: a step of preparing copper particles; a step of coating the copper particles with carboxylic acids; and a step of adding the copper particles coated with carboxylic acids to a dispersion medium and dispersing them using a bead mill or a high-pressure wet micronization device.
[0023] A fifth aspect of the present invention is the production method according to the fourth aspect, wherein the dispersing step is performed under an inert gas atmosphere.
[0024] Aspect 6 of the present invention is the production method according to aspect 4, wherein the dispersing step is performed under atmospheric air.
[0025] Aspect 7 of the present invention is the production method according to any one of aspects 4 to 6, wherein the rotation speed of the agitator of the bead mill is 1000 rpm or more and less than 3000 rpm.
[0026] Aspect 8 of the present invention is a method for producing a sintered copper microparticle body, comprising: heating the oxide-containing copper microparticles according to any one of aspects 1 to 3 to 100° C. to 200° C. in an inert gas atmosphere.
[0027] Aspect 9 of the present invention is the manufacturing method described in aspect 8, wherein the inert gas contains N2.
[0028] Scheme 10 of the present invention is the manufacturing method described in Scheme 9, wherein the inert gas is mixed with less than 4 volume % of H2.
[0029] Effects of the Invention
[0030] According to an embodiment of the present invention, the following copper particles and a method for producing the same, as well as a method for producing a sintered body using the copper particles, can be provided. The copper particles do not require two-stage heating and additional copper material, and can obtain a sintered body showing sufficient conductivity by a single heating at a temperature below 200° C. under normal pressure (or a pressure above it). BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD spectrum of the oxide-containing copper fine particles of Sample No.1.
[0032] Figure 2 This is the XRD spectrum of the oxide-containing copper fine particles of Sample No.2.
[0033] Figure 3 This is a high-resolution TEM image of the oxide-containing copper particles of Sample No. 1.
[0034] Figure 4 This is a high-resolution TEM image of the oxide-containing copper particles of Sample No. 2.
[0035] Figure 5 This is a SEM image of a sintered body of the oxide-containing copper fine particles of Sample No. 1, which was heated to 120° C. in an atmosphere of a mixed gas of nitrogen and hydrogen with a purity of 4N (hydrogen concentration: 3 vol %) at normal pressure.
[0036] Figure 6 This is a SEM image of a sintered body of the oxide-containing copper fine particles of Sample No. 1, which was heated to 200° C. in an atmosphere of a mixed gas of nitrogen and hydrogen with a purity of 4N (hydrogen concentration: 3 vol %) at normal pressure.
[0037] Figure 7 This is a temperature and pressure profile when copper cylindrical test piece 1 and copper cylindrical test piece 2 are joined without pressurization using oxide-containing copper fine particles of sample No. 3.
[0038] Figure 8 This is a schematic diagram for explaining a method for measuring the adhesive strength when the copper column test piece 1 and the copper column test piece 2 are joined together using the oxide-containing copper microparticles of Sample No. 3.
[0039] Fig. 9 This is a graph showing the results of measuring the bonding strength when copper cylindrical test piece 1 and copper cylindrical test piece 2 were bonded together without applying pressure using the oxide-containing copper microparticles of sample No. 3.
[0040] Fig.10 yes Fig. 9 Optical microscope image of the fracture surface of the copper cylinder test piece 1 after the bonding strength measurement.
[0041] Fig.11 yes Fig. 9 Optical microscope image of the fracture surface of the copper cylinder test piece 2 after the bonding strength measurement.
[0042] Fig.12 yes Fig. 9 FE-SEM image of the fracture surface of the copper cylindrical test piece 2 after the bonding strength measurement.
[0043] Fig.13 This is a measurement line of temperature and pressure when the copper cylindrical test piece 1 and the copper cylindrical test piece 2 are press-bonded using the oxide-containing copper fine particles of Sample No. 3.
[0044] Fig.14 This is a graph showing the results of measuring the adhesive strength when the copper cylindrical test piece 1 and the copper cylindrical test piece 2 were press-bonded using the oxide-containing copper microparticles of Sample No. 3.
[0045] Fig.15 yes Fig.14 Optical microscope image of the fracture surface of the copper cylinder test piece 1 after the bonding strength measurement.
[0046] Fig.16 yes Fig.14 Optical microscope image of the fracture surface of the copper cylinder test piece 2 after the bonding strength measurement.
[0047] Fig.17 yes Fig.14 FE-SEM image of the fracture surface of the copper cylindrical test piece 2 after the bonding strength measurement. DETAILED DESCRIPTION
[0048] The present inventors have studied from various perspectives to achieve copper microparticles that can obtain a sintered body exhibiting sufficient conductivity by a single heating at 200° C. or below under normal pressure (or pressures above it), without requiring two-stage heating and additional copper material.
[0049] As a result, it was found that by containing Cu in a specific mass ratio in the copper particles 64 O and coated with carboxylic acid, when heated below 200°C under normal pressure (or pressure above), the flux of carboxylic acid will 64 O is reduced, and copper particles are easily combined with each other (necking). As a result, a sintered body showing sufficient conductivity can be obtained by a single heating at 200°C or below under normal pressure (or a pressure higher than that) without the need for two-stage heating and additional copper material as in the prior art.
[0050] The following describes the details of each requirement stipulated in the embodiment of the present invention.
[0051] The oxide-containing copper particles according to the embodiment of the present invention include Cu 64 O and Cu2O as needed, and is coated with carboxylic acids, Cu 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is 0.5 to 2.0 mass%. That is, the copper particles containing oxides may not contain Cu2O. In this case, Cu 64 O relative to Cu and Cu 64 The total mass ratio of O can be set to 0.5 to 2.0 mass %. On the other hand, the copper particles containing oxides may contain Cu2O. In this case, Cu 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O may be set to 0.5 to 2.0 mass %.
[0052] In Cu 64 O relative to Cu, Cu 64 When the mass ratio of the total mass of O and Cu2O is less than 0.5 mass%, 64 Insufficient O content will inhibit the diffusion of copper atoms during heating, weaken the bonding between copper particles, and the conductivity of the sintered body obtained by a single heating at normal pressure (or pressure above) and below 200°C may become insufficient. 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is set to 0.5 mass% or more, preferably 1.0 mass% or more.64 O relative to Cu, Cu 64 When the mass ratio of the total mass of O and Cu2O exceeds 2.0 mass%, Cu 64 Excessive O content makes it impossible to fully reduce Cu in a single heating at normal pressure (or pressure above) and below 200°C. 64 O, the electrical conductivity of the obtained sintered body may become insufficient.
[0053] The oxide-containing copper particles according to the embodiment of the present invention may contain Cu2O as needed. 64 O is less likely to be reduced by the action of carboxylic acid flux, but at least a part of it can be reduced at a relatively high temperature of 180°C or more, preferably 200°C or more, under normal pressure (or pressure above). 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is 0.5 to 2.0 mass %, and Cu2O is further included on this basis, and heating at a relatively high temperature can promote the necking of copper particles and improve the conductivity of the resulting sintered body.
[0054] A preferred embodiment of the present invention is to use Cu2O relative to Cu, Cu 64 The mass ratio of the total mass of CuO and Cu2O is set to be 0 mass% or more and less than 0.5 mass%. That is, Cu2O is not contained (Cu2O is relative to Cu, Cu 64 O and Cu2O have a mass ratio of 0 mass %), or Cu2O is included and Cu 64 O relative to Cu and Cu 64 The mass ratio of the total mass of O is set to be more than 0 mass % and less than 0.5 mass %. This makes it possible to obtain a sintered body that exhibits sufficient conductivity even when heated at a lower temperature (for example, 120° C. or less).
[0055] Another preferred embodiment of the present invention is to use Cu2O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is set to 0.5 to 2.0 mass %. Thus, by heating at a high temperature of, for example, 180°C or higher, or further 200°C or higher, a sintered body having higher conductivity can be obtained.
[0056] In the oxide-containing copper fine particles according to the embodiment of the present invention, Cu 64 O and Cu2O relative to Cu, Cu 64The mass ratio of the total mass of O and Cu2O can be calculated by obtaining an XRD pattern and using the RIR (Reference Intensity Ratio) method. The RIR method is a method of calculating a quantitative value using the RIR value recorded in a database based on the integrated intensity obtained from the strongest line of the component being tested after deducting the background intensity determined by the extraction baseline. In an embodiment of the present invention, the strongest lines of each component (Cu(111), Cu 64 O(044) and Cu2O(111)) and the integrated intensity and RIR values (Cu: 8.86, Cu 64 O: 4.89, Cu2O: 8.28), and the mass ratio was calculated. It should be noted that Cu(111) has a diffraction peak at 2θ=43.298°, and Cu 64 O(044) has a diffraction peak at 2θ=40.710°, and Cu2O(111) has a diffraction peak at 2θ=36.419°.
[0057] A preferred embodiment of the present invention is that the copper particles containing oxides are composed of Cu, Cu 64 O and inevitable impurities, Cu 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O is 0.5 to 2.0 mass %, and the copper fine particles containing oxides are coated with carboxylic acids. The inevitable impurities are preferably 2.0 mass % or less, more preferably 1.0 mass % or less. This can improve the conductivity of the sintered body.
[0058] Another preferred embodiment of the present invention is that the copper particles containing oxides are composed of Cu, Cu 64 O, Cu2O and inevitable impurities, Cu 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is 0.5-2.0 mass %, and the mass ratio of Cu2O to Cu, Cu 64 The mass ratio of the total mass of CuO and Cu2O is greater than 0 mass % and less than 0.5 mass %, and the oxide-containing copper particles are coated with carboxylic acids. Another preferred embodiment of the present invention is that the oxide-containing copper particles are composed of Cu, Cu 64 O, Cu2O and inevitable impurities, Cu 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is 0.5-2.0 mass %, and the mass ratio of Cu2O to Cu, Cu 64The mass ratio of the total mass of O and Cu2O is 0.5 to 2.0 mass %, and the copper particles containing oxides are coated with carboxylic acids. The inevitable impurities are preferably 2.0 mass % or less, and more preferably 1.0 mass % or less. Thus, the conductivity of the sintered body can be improved.
[0059] It should be noted that unavoidable impurities refer to elements introduced due to conditions such as raw materials, materials, and manufacturing equipment.
[0060] In an embodiment of the present invention, Cu is preferably 64 O exists on the surface of the copper particles containing oxide. 64 O exists on the surface of the copper particles containing oxides, and the surface is coated with carboxylic acid. This can promote the necking of the copper particles when heated at low temperatures (e.g., below 120°C). In this case, it is preferred that Cu exists on the surface of the copper particles containing oxides. 64 O has a thickness of 5 nm or less from the surface. Therefore, especially when heated at a low temperature (e.g., 120° C. or less), the carboxylic acid flux can easily reduce Cu 64 O.Cu 64 The lower limit of the thickness of O from the surface is not particularly limited, and may be, for example, 0.1 nm or more.
[0061] In an embodiment of the present invention, Cu 64 Whether O exists on the surface of the copper particles containing oxides can be determined by Figure 3 and Figure 4 This was confirmed by high-resolution TEM images of the ends of copper particles containing oxides. 64 The lattice fringe spacing (inter-plane spacing) of the O(044) plane and the Cu2O(111) plane are as well as Therefore, it is possible to distinguish Cu and Cu based on the difference in lattice fringe spacing that appears in high-resolution TEM images. 64 O and Cu2O can confirm whether there is Cu at the end (surface) of the copper particle containing oxide. 64 O.
[0062] The average particle size of the oxide-containing copper particles of the embodiment of the present invention is preferably 20 to 300 nm. Here, "particle size" refers to the primary particle size and equivalent circle diameter of the oxide-containing copper particles, and "average particle size" refers to the median diameter. By making the average particle size moderately large, the cohesive force between the particles is reduced, for example, when dispersed in a dispersion medium, the oxide-containing copper particles become easy to disperse. In addition, by making the average particle size moderately large, the surface area can be reduced as a whole, so the coating amount of carboxylic acids as insulators can also be reduced, and the conductivity of the sintered body can be easily improved. Furthermore, the surface area can be reduced as a whole, so unnecessary excessive surface oxidation can also be suppressed. On the other hand, by making the average particle size moderately small, it is easy to obtain a sintered body with a uniform surface, which not only reduces the volume resistivity of the sintered body, but also improves high-speed transmission. This phenomenon is caused by the epidermal effect. That is, in high-frequency signals, current concentration occurs on the surface of the conductor, so if the surface of the sintered body is rough, the transmission path is extended and the loss becomes larger. By reducing the average particle size of the copper particles constituting the sintered body, the surface roughness becomes smaller, and it is easy to ensure the uniformity of the sintered body.
[0063] The average particle size can be determined by randomly photographing at least 10 oxide-containing copper microparticles using a scanning electron microscope (SEM) and measuring the particle sizes thereof.
[0064] The shape of the oxide-containing copper particles according to the embodiment of the present invention is not particularly limited, and may be spherical, ellipsoidal, polygonal (polygonal pyramidal, cubic, rectangular, etc.), plate-like, rod-like and / or irregular in shape, and isotropic shapes such as spherical are preferred from the perspective of excellent dispersibility.
[0065] In the embodiment of the present invention, the Cu 64 O and Cu2O reduction according to the situation. As carboxylic acids for coating the oxide-containing copper particles of the embodiment of the present invention, for example, saturated fatty acids, unsaturated fatty acids, hydroxy acids, aromatic carboxylic acids, terpene carboxylic acids, etc. can be listed, and one can be used alone or in combination of two or more. As carboxylic acids, it is preferred to use at least one selected from aliphatic monocarboxylic acids, aliphatic dicarboxylic acids, aromatic carboxylic acids and terpene carboxylic acids. In addition, carboxylic acids are preferably hydrophobic. By being hydrophobic, the equilibrium reaction represented by the following formula (1) during storage (non-heating) can be suppressed, and the reaction by H3O + The corrosion reaction caused by it.
[0066]
[0067] In the above formula (1), R is, for example, a monovalent hydrocarbon group.
[0068] As aliphatic monocarboxylic acids, aliphatic monocarboxylic acids having 5 or more carbon atoms are preferred because they show hydrophobicity. The aliphatic monocarboxylic acid may be any of a straight chain or a branched chain, and may also be any of a saturated aliphatic monocarboxylic acid and an unsaturated aliphatic monocarboxylic acid. Among them, a straight chain saturated aliphatic monocarboxylic acid is preferred. In addition, the carbon number of the aliphatic monocarboxylic acid is preferably 5 to 18. The aliphatic monocarboxylic acid may be used alone or in combination of two or more. As aliphatic monocarboxylic acids, hexanoic acid (6 carbon atoms), caprylic acid (8 carbon atoms), capric acid (10 carbon atoms), lauric acid (12 carbon atoms), myristic acid (14 carbon atoms), palmitic acid (16 carbon atoms), stearic acid (18 carbon atoms), etc., which have an even number of carbon atoms, are inexpensive and easily available, and are preferred.
[0069] As aliphatic dicarboxylic acids, aliphatic dicarboxylic acids having 6 or more carbon atoms are preferred because they show hydrophobicity. The aliphatic dicarboxylic acid may be any of a straight chain or a branched chain, and may be any of a saturated aliphatic dicarboxylic acid and an unsaturated aliphatic dicarboxylic acid. Among them, a straight chain saturated aliphatic dicarboxylic acid is preferred. In addition, the carbon number of the aliphatic dicarboxylic acid is preferably 6 to 18. The aliphatic dicarboxylic acid may be used alone or in combination of two or more. Examples of aliphatic dicarboxylic acids include adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,0-nonane dicarboxylic acid, 1,10-decane dicarboxylic acid, brassylic acid, 1,12-dodecane dicarboxylic acid, 1,13-tridecane dicarboxylic acid, thhapsic acid, 1,15-pentadecanedicarboxylic acid, 1,16-hexadecane dicarboxylic acid, and the like.
[0070] Examples of the aromatic carboxylic acid include benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, hemimellitic acid, trimellitic acid, and trimesic acid.
[0071] As the terpene carboxylic acid, there can be used a terpene carboxylic acid contained in rosin, etc. Examples thereof include abietic acid, neoabietic acid, palustric acid, pimaric acid, isopimaric acid, and dehydroabietic acid.
[0072] In an embodiment of the present invention, whether the carboxylic acid covers the oxide-containing copper particles can be confirmed by a known mass spectrometry method, for example, by ionizing the surface carboxylic acid by laser desorption ionization (Laser Desorption Ionization: LDI) and determining the mass-to-charge ratio by time of flight measurement (Time of Flight: TOF).
[0073] The method for producing oxide-containing copper particles according to an embodiment of the present invention includes: preparing copper particles; coating the copper particles with carboxylic acids; adding the copper particles coated with carboxylic acids to a dispersion medium and dispersing them using a bead mill or a high-pressure wet micronizer.
[0074] Hereinafter, each step will be described in detail.
[0075] <1. Process of preparing copper microparticles>
[0076] The method for preparing copper particles is not particularly limited, and gas phase methods (sputtering, evaporation, plasma method, etc.) or liquid phase methods (chemical reduction, thermal decomposition, polyol method, etc.) can be listed. The purity of the copper particles is preferably 98.0% by mass or more, and more preferably 99.0% by mass or more. Thus, the conductivity of the sintered body can be provided. In addition, the average particle size of the copper particles is preferably set to 20 to 300 nm. In the case of preparing copper particles by chemical reduction, the copper compound is dispersed or dissolved in a solvent, and then a reducing agent and a carboxylic acid are added to the solvent, and then a reduction reaction of the copper compound is carried out, thereby simultaneously carrying out the process of coating with carboxylic acids described later.
[0077] <2. Carboxylic acid coating step>
[0078] By mixing the copper particles and the carboxylic acid, the copper particles can be coated with the carboxylic acid. When mixing, if the carboxylic acid is a liquid, the copper particles can be added to the carboxylic acid for mixing. If the carboxylic acid is a solid, the carboxylic acid can be dissolved in an appropriate solvent and then the copper particles can be added for mixing. The temperature during mixing is preferably set to 25 to 90° C., and the mixing time is preferably set to 10 to 180 minutes.
[0079] Hereinafter, an example of <1. step of preparing copper microparticles> and <2. step of coating with carboxylic acid> according to an embodiment of the present invention will be described.
[0080] First, a copper compound is dispersed or dissolved in a solvent, a carboxylic acid and a reducing agent are added to the solvent, and the mixture is reacted under conditions such as elevated temperature for a reduction reaction to generate copper microparticles coated with the carboxylic acid.
[0081] As the solvent, lower alcohols such as methanol, ethanol, and 2-propanol, which have a lower polarity than water, and ketones such as acetone can be used. These can be used alone or in combination of two or more.
[0082] As copper compounds, copper oxide (CuO), cuprous oxide (Cu2O), copper hydroxide (Cu(OH)2), etc., which are dispersed in the form of particles in a solvent, or anhydrides or hydrates of copper formate (Cu(HCOO)2), copper acetate (Cu(CH3COO)2), copper sulfate (CuSO4), etc., which are dissolved in a solvent in part or in whole to form a copper ion solution, can be used.
[0083] The amount of the copper compound added depends on the type of the copper compound and is not particularly limited, but is preferably added so that the copper ion concentration is 0.01 to 5 mol / L, more preferably 0.1 to 3 mol / L, from the viewpoint of productivity of copper particles and suppression of viscosity increase of the reaction solution.
[0084] The amount of carboxylic acid added depends on the chain length, etc., but from the viewpoint of controlling the coating amount on copper fine particles, for example, it is preferably in the range of 0.0001 to 4 equivalents, more preferably 0.002 to 0.1 equivalents, relative to copper ions in the solvent.
[0085] Examples of the reducing agent include hydrazine-based reducing agents such as hydrazine, hydrazine hydrochloride, hydrazine sulfate, and hydrazine hydrate; hydroborates such as sodium borohydride; citric acid, and ascorbic acid. The amount of the reducing agent added may be determined stoichiometrically in consideration of the reaction with the copper compound.
[0086] By heating the solvent in which the copper compound is dispersed or dissolved, the copper compound is reduced to the metal core of the copper microparticles to generate copper microparticles coated with carboxylic acid. The heating temperature is preferably 25 to 90° C., and the heating time is preferably 10 to 300 minutes.
[0087] After the reaction is completed, the copper fine particles coated with the carboxylic acid may be washed and purified with an organic solvent, and then separated, dried, etc. as appropriate.
[0088] <3. Dispersion process using a bead mill or high-pressure wet micronizer>
[0089] The copper particles coated with carboxylic acid generated as described above are added to a dispersion medium and dispersed using a bead mill or a high-pressure wet micronizer. In this process, during the dispersion using a bead mill or a high-pressure wet micronizer, the copper particles can be appropriately oxidized by the carboxylic acid and the dispersion medium, and as a result, Cu 64 O (Cu2O is also generated depending on the situation), and can make Cu 64 O relative to Cu, Cu 64The mass ratio of the total mass of O and Cu2O is 0.5 to 2.0% by mass. It should be noted that the high-pressure wet atomization device is a device that atomizes by extruding (dispersion medium) from a plunger connected to a supercharger at high pressure and colliding with ceramic balls in a container filled with a liquid (dispersion medium). For example, STAR BURST mini (manufactured by SUGINO MACHINE Co., Ltd.) can be cited. The dispersion by the high-pressure wet atomization device is less contaminated by beads or the like during dispersion compared to the dispersion by a bead mill, and is preferred.
[0090] As the dispersion medium, from the viewpoint of enabling high-concentration dispersion of copper fine particles (and copper fine particles containing oxides generated by their oxidation), an organic solvent is preferred. As the organic solvent, for example, alcohol solvents such as alkanols, aliphatic polyols, alicyclic alcohols, amine solvents, ester solvents such as acetate esters, ketone solvents such as chain ketones and cyclic ketones, ether solvents such as chain ethers and cyclic ethers, aromatic solvents such as aromatic hydrocarbons, halogen solvents such as halogenated alkanes, nitrile solvents, nitro solvents, etc. can be cited. They can be used alone or in combination of two or more. Regarding the viscosity of the dispersion medium, when it is 0.1 Pa·s or more, the dispersibility of copper fine particles (and copper fine particles containing oxides generated after their oxidation) is improved, and thus it is preferred.
[0091] From the viewpoint of production efficiency, the addition amount of copper fine particles in the dispersion medium is preferably 30% by mass or more, more preferably 50% by mass or more, for example. There is no particular limitation on the upper limit of this addition amount, but in the case of assuming use as a coating liquid later, from the viewpoint of coatability, it is preferably 90% by mass or less, more preferably 80% by mass or less. In order to increase the addition amount of copper fine particles in the dispersion medium and disperse them, it is only necessary to appropriately adjust the viscosity of the dispersion medium, the material (density) of the beads, the bead diameter (the number of beads), and the rotation speed, etc. Regarding various conditions (such as ejection pressure and number of passes, etc.) in the case of using a high-pressure wet atomization device, it is only necessary to appropriately adjust according to the specifications of the device used. For example, in the case of using STARBURST mini (SUGINO MACHINE Co., Ltd.), the ejection pressure can be set to 100 to 245 MPa, and the number of passes is not particularly limited, but from the viewpoint of productivity, it can be set to 1 to 20 times.
[0092] The dispersion medium may contain various additives as needed. As the additives, coupling agents, dispersants, colorants, hue improvers, dye fixing materials, gloss imparting agents, etc. can be cited.
[0093] The atmosphere during bead mill dispersion can be set to an inert gas atmosphere or the atmosphere. The pressure is not particularly limited. By dispersing in an inert gas atmosphere, it is possible to generate Cu2O-free, or the relative content of Cu2O to Cu, Cu64 O and Cu2O have a mass ratio of less than 0.5 mass% of oxide-containing copper particles. As inert gases, nitrogen, argon, helium, etc. can be listed. The higher the purity, the more Cu2O-containing copper particles can be generated. As an inert gas, N2 is preferred from the perspective of being cheap and easy to obtain, and N2 with a purity of 4N or more is more preferred. On the other hand, by dispersing in the atmosphere, Cu2O can be generated relative to Cu, Cu 64 The oxide-containing copper particles have a mass ratio of 0.5 mass % or more of the total mass of O and Cu2O. Since the system of the high-pressure wet atomization device is filled with liquid (dispersion medium), there is no particular restriction on the atmosphere during dispersion by the high-pressure wet atomization device.
[0094] In order to suppress the reaction of carboxylic acids with the dispersion medium, for example, the temperature during the dispersion by the bead mill is preferably set to room temperature. During the dispersion, it can be carried out while being appropriately cooled so as not to become high temperature due to the influence of friction between the beads, collision with ceramic balls, etc. During the dispersion by the high pressure wet micronizing device, it can be carried out while being appropriately cooled so as not to become high temperature due to the influence of collision with ceramic balls, etc.
[0095] As the material of the beads of the bead mill, silica, alumina, zirconia, etc. can be used. Zirconia is preferably used from the viewpoints of high density and wear resistance. There is no particular restriction on the bead diameter, which can be appropriately adjusted according to other conditions such as the amount of copper particles added, for example, it can be set to 1 μm to 2 mm.
[0096] The rotation speed of the stirring member (agitator) of the bead mill is preferably lower than 3000 rpm from the perspective of suppressing excessive oxidation, deformation, fusion, integration and overdispersion of the copper particles. On the other hand, from the perspective of removing the agglomeration of the copper particles, dispersing them, and properly oxidizing the surface, it is preferably set to more than 1000 rpm. In addition, the rotation speed can also be changed to perform multiple dispersions, for example, it can also be rotated at 1000 to 1500 rpm first, and after a certain degree of dispersion, the rotation speed is increased to 1500 to 2500 rpm for dispersion.
[0097] The dispersion time in the bead mill is not particularly limited and may be appropriately adjusted depending on other conditions such as the amount of copper fine particles added, the dispersion medium, and the diameter of beads used in the bead mill, and can be set to, for example, 10 to 180 minutes.
[0098] After the dispersion by the bead mill is completed, the beads and the copper particles containing oxides are separated using an appropriate separator. It should be noted that when using a high-pressure wet micronizing device, unlike a bead mill, the ceramic balls do not enter the dispersion, so there is no need to separate the ceramic balls from the copper particles containing oxides.
[0099] As described above, the oxide-containing copper microparticles according to the embodiment of the present invention dispersed in the dispersion medium can be obtained. The dispersion medium can be removed by drying or the like as necessary.
[0100] The method for producing oxide-containing copper microparticles according to the embodiment of the present invention may include other steps within the scope of achieving the object of the embodiment of the present invention.
[0101] As described above, the method for producing the oxide-containing copper particles according to the embodiment of the present invention has been described. A person skilled in the art who understands the desired properties of the oxide-containing copper particles according to the embodiment of the present invention may find a method for producing the oxide-containing copper particles according to the embodiment of the present invention, i.e., a method other than the above-mentioned production method, by repeated experiments.
[0102] The method for producing a sintered copper microparticle body according to an embodiment of the present invention includes a step of heating the oxide-containing copper microparticles produced as described above to 100° C. to 200° C. in an inert gas atmosphere for sintering. The above-mentioned "inert gas atmosphere" may be at normal pressure (or a pressure higher than normal pressure) (i.e., it may be normal pressure or a state pressurized than normal pressure).
[0103] In an embodiment of the present invention, sintering can be performed under an inert gas atmosphere. The pressure of the atmosphere can be normal pressure (or a pressure above it). Heating under an inert gas atmosphere is different from heating under vacuum, and has the advantages of no need for intermittent processing and high productivity. As an inert gas, nitrogen, argon, helium, etc. can be listed. From the perspective of being cheap and easily available, it is preferred that nitrogen (N2) be included, and it is more preferred that the inert gas be composed of high-purity (e.g., 4N or more) N2. In addition, from the perspective of improving the electrical conductivity of the sintered body, a reducing gas such as hydrogen (H2) can also be mixed in the inert gas. H2 can be mixed with the inert gas at a lower explosion limit (4 volume %), for example, it can be mixed at 3 volume % or less. Preferably, the inert gas is composed of high-purity (e.g., 4N or more) N2, and H2 is further mixed in the inert gas at 3 volume % or less.
[0104] In an embodiment of the present invention, sintering can be performed at a temperature below 200°C. From the viewpoint of heat resistance of the substrate, etc., the lower the heating temperature, the more preferred. On the other hand, from the viewpoint of productivity, for example, it is preferably set to above 100°C. It is more preferably above 120°C, and further preferably above 150°C. Thus, the heating time can be shortened. In the case where the heat resistance of the substrate, etc. is high depending on the application, it can be heated to more than 200°C from the viewpoint of improving the conductivity of the sintered body.
[0105] In the embodiment of the present invention, the heating sintering time can be appropriately adjusted according to the heating temperature and the thickness of the sintered body of the copper microparticles, and can be, for example, 180 minutes or less. From the viewpoint of productivity, it is preferably 120 minutes or less.
[0106] In the manufacturing method of the copper particle sintered body of the embodiment of the present invention, the copper particles containing oxides of the embodiment of the present invention can be directly heated to generate a sintered body, or the particles can be dispersed in a dispersion medium, the dispersion liquid is applied to a substrate and heated to generate a sintered body. As a dispersion medium, from the viewpoint of enabling the copper particles containing oxides to be dispersed at a high concentration, an organic solvent is preferably used. As an organic solvent, for example, alcohol solvents such as alkanols, aliphatic polyols, alicyclic alcohols, ester solvents such as amine solvents, acetates, ketone solvents such as chain ketones, cyclic ketones, ether solvents such as chain ethers, cyclic ethers, aromatic solvents such as aromatic hydrocarbons, halogen solvents such as alkyl halides, nitrile solvents, nitro solvents, etc. can be listed. They can be used alone or in combination of two or more. Assuming that the dispersion liquid is used for screen printing, the dispersion medium can be set to polyols with high viscosity such as ethylene glycol, propylene glycol, and glycerol. Assuming that the dispersion liquid is used for inkjet printing, the dispersion medium can be set to lower alcohols with low viscosity such as methanol, ethanol, and 2-propanol. In addition, directly using the dispersion medium used in the method for producing copper particles containing oxides according to an embodiment of the present invention can simplify the process, which is preferred.
[0107] The dispersion may contain various additives as required, and examples of the additives include coupling agents, dispersants, colorants, hue improvers, dye fixing agents, gloss imparting agents, and the like.
[0108] The substrate can be made of organic or inorganic materials. As organic materials, for example, polymethyl methacrylate resins, polypropylene resins, cyclic polyolefin resins, styrene resins, vinyl chloride resins, polyester resins, polyamide resins, polycarbonate resins, polysulfone resins, polyethersulfone resins, polyimide resins, cellulose derivatives, fluororesins, phenolic resins, epoxy resins, etc. As inorganic materials, for example, soda-lime glass, borosilicate glass, crown glass, barium-containing glass, strontium-containing glass, boron-containing glass, low-alkali glass, alkali-free glass, crystallized transparent glass, silica glass, quartz glass, and heat-resistant glass, and metal oxides such as aluminum oxide, sapphire, zirconium oxide, titanium dioxide, yttrium oxide, indium oxide-tin oxide composite oxide (ITO), fluorine-doped tin oxide (FTO), and antimony-doped zinc oxide (AZO), etc. They can be a single type or a composite material composed of two or more. The thickness of the substrate is not particularly limited, but is preferably 5 mm or less in consideration of heat transfer when heating is performed via the substrate.
[0109] As the coating method of the dispersion, a conventional method can be used. In the case of forming a pattern such as wiring, for example, screen printing, inkjet printing, gravure printing, offset printing, gravure offset printing, relief printing, flexographic printing, reverse printing, etc. can be used. The formation of the wiring pattern can be carried out, for example, by coating the dispersion on the substrate in a manner to form a desired pattern and heating it under the above conditions.
[0110] The coating amount is not particularly limited, and can be, for example, 1 to 100 g / m 2 The thickness of the sintered body is not particularly limited, but can be, for example, 1 to 100 μm.
[0111] Example
[0112] The following examples are given to more specifically describe the embodiments of the present invention. The embodiments of the present invention are not limited to the following examples, and can be implemented with appropriate changes within the scope of the above and the following purports, which are all included in the technical scope of the embodiments of the present invention.
[0113] In a 1L flask, 100mL of solvent alcohol (2-propanol or ethanol) was added to 0.1mol of raw material copper oxide (CuO, manufactured by NISSIN CHEMCO), and hexanoic acid was added in a range of 2 to 6mmol while being fully stirred with a stirring blade. After heating to 70°C in a water bath, 0.2mol of hydrazine monohydrate was added and reacted for 1 to 2 hours. After the reaction, after cooling to room temperature, the supernatant was removed by centrifugation, and the same operation was performed using solvents such as ethanol, acetone, and methanol to purify the copper particles. Finally, the powder was fully dried using a nitrogen stream and recovered. The water contact angle of the obtained powder was measured, and the results showed high hydrophobicity, confirming that the surface of the particles was coated with hexanoic acid. In addition, the XRD spectrum of the obtained powder was obtained, and the purity of copper (Cu) was analyzed by the RIR method, and the result was more than 99.0% by mass.
[0114] The copper particles are added to the dispersion medium and dispersed using a bead mill (manufactured by NIPPON COKE & ENGINEERING (KK), product name: POWDER LAB). Dipropylene glycol is used as a dispersion medium, and the content of the copper particles is 50% by mass. The material of the beads is zirconium oxide (ZrO2), and the bead diameter is 0.03 mm. As for dispersion, the sample No. 1 is carried out under a nitrogen atmosphere with a purity of 4N, and the sample No. 2 is carried out under the atmosphere. The room temperature is maintained during dispersion, and the speed of the agitator of the bead mill is initially 1000 rpm for 30 minutes of dispersion, and then at 2000 rpm for 30 minutes. After the dispersion is completed, the zirconium oxide beads are separated by a separator to obtain oxide-containing copper particles (samples No. 1 and 2) dispersed in dipropylene glycol and coated with hexanoic acid.
[0115] The XRD patterns of the oxide-containing copper microparticles of Sample Nos. 1 and 2 were obtained. The XRD patterns were obtained by applying the dispersions of the oxide-containing copper microparticles of Sample Nos. 1 and 2 directly to the sample substrate. Figure 1 and 2 The XRD patterns of samples No. 1 and 2 are shown respectively. Figure 1 and Figure 2 Among them, only Cu, Cu 64 O and Cu2O peaks. It can be said that the inevitable impurities are at most 1.0 mass % or less.
[0116] Regarding Cu of Sample No. 1 and 2 64 O and Cu2O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is calculated using the RIR method. Figure 1 and 2 The strongest lines of each component (Cu(111), Cu 64O(044) and Cu2O(111)) after deducting the background intensity determined by the extraction baseline and the RIR values (Cu: 8.86, Cu 64 O: 4.89, Cu2O: 8.28) to calculate the mass ratio. It should be noted that Cu(111) has a diffraction peak at 2θ=43.298°, and Cu 64 O(044) has a diffraction peak at 2θ=40.710°, and Cu2O(111) has a diffraction peak at 2θ=36.419°.
[0117] High-resolution TEM images of the ends of the oxide-containing copper particles of Samples No. 1 and 2 were obtained. The TEM samples were obtained by diluting the dispersion of the oxide-containing copper particles of Samples No. 1 and 2, applying the diluted dispersion on a high-resolution TEM carbon-coated grid, and vacuum drying the diluted dispersion. Figure 3 and 4 The high-resolution TEM images of samples No. 1 and 2 are shown respectively. It should be noted that in the basic application (Japanese patent application, Japanese patent application No. 2020-144680), Figure 3 and Figure 4 , the original drawing is submitted together with this application as a case filing document so that the difference in lattice fringes can be understood in more detail. You can also refer to the original drawing as needed.
[0118] exist Figure 3 and Figure 4 In the figure, the region indicated by 1 is a region where lattice fringes corresponding to the interplanar spacing of Cu(111) are confirmed, and the region indicated by 2 is a region where lattice fringes corresponding to the interplanar spacing of Cu(111) are confirmed. 64 The region shown in 3 is a region where lattice fringes corresponding to the interplanar spacing of Cu2O(111) are confirmed. Figure 3 and Figure 4 In the experiment, it was confirmed that Cu and Cu 64 O and Cu2O.
[0119] The oxide-containing copper particles of Sample No. 1 and 2 dispersed in dipropylene glycol were coated on an alumina substrate, and heated for 60 minutes under a total of six conditions, namely, two heating atmospheres (nitrogen atmosphere with a purity of 4N, or a mixed gas atmosphere of nitrogen and hydrogen with a purity of 4N (hydrogen concentration 3 volume %)) and three heating temperatures (120°C, 150°C, and 200°C) at normal pressure to obtain a sintered body. The volume resistivity of the obtained sintered body was measured by a four-probe method using a resistivity meter (Loresta GP manufactured by Mitsubishi Chemical Analytech). The results are shown in Table 1. It should be noted that in Table 1, in the "Atmosphere" column of the "Heating Conditions", the case of heating in a nitrogen atmosphere with a purity of 4N is recorded as "N2", and the case of heating in an atmosphere of a mixed gas of nitrogen and hydrogen with a purity of 4N (hydrogen concentration 3 volume %) is recorded as "N2-H2 (3%)". In addition, when the heating conditions of sample No. 2 were "pressure: normal pressure, heating temperature: 120°C, atmosphere: N2", the resistance value of the sintered body was very high (>10 7 Ω), the volume resistivity could not be measured, and thus “-” was recorded in the volume resistivity column.
[0120] [Table 1]
[0121]
[0122] The results in Table 1 can be considered as follows. Samples No. 1 and 2 in Table 1 are examples that satisfy all the necessary conditions specified in the embodiments of the present invention. The volume resistivity is 5.0×10 -4 Ω·cm or less, and a sintered body showing sufficient conductivity was obtained.
[0123] Sample No. 1 meets the necessary conditions of a preferred embodiment of the present invention, that is, Cu2O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is 0 mass % or more and less than 0.5 mass %, and is 1.0×10 -4 Ω·cm or less, and a sintered body showing high electrical conductivity was obtained, and the conductivity was 5.0×10 -4 Ω·cm or less, and a sintered body showing sufficient conductivity was obtained.
[0124] Sample No. 2 meets the necessary conditions of another preferred embodiment of the present invention, that is, the ratio of Cu2O to Cu and Cu 64 The mass ratio of the total mass of O and Cu2O is 0.5-2.0 mass %. When heated at 200°C under normal pressure, the volume resistivity is 1.5×10 -5 Ω·cm or less, a sintered body showing higher conductivity was obtained.
[0125] In Samples No. 1 and 2, by mixing the reducing gas H 2 with the inert gas N 2 during heating, the volume resistivity becomes lower than the case where H 2 is not contained, except for the heating at 120° C. in Sample No. 1.
[0126] Figure 5 FIG. 2 shows an SEM image of a sintered body of oxide-containing copper particles of Sample No. 1 after heating to 120° C. in an atmosphere of a nitrogen and hydrogen mixture gas with a purity of 4N (hydrogen concentration 3 vol%) at normal pressure. Figure 6 2 shows an SEM image of a sintered body of the oxide-containing copper particles of Sample No. 1 heated to 200° C. in an atmosphere of a nitrogen and hydrogen mixture gas (hydrogen concentration 3 vol%) at a normal pressure. Figure 5 (Heated at 120°C, volume resistivity: 4.6×10 -4 Ω·cm) compared to Figure 6 (Heated at 200°C, volume resistivity: 1.9×10 -5 Ω·cm), it was observed that the copper particles were well necked together.
[0127] Furthermore, the oxide-containing copper particles of sample No. 3 were prepared as follows, and the bonding strength of the sample No. 3 as a bonding material was investigated. The background of investigating the bonding strength is that due to the increase in the operating temperature of power semiconductors in recent years, the melting point of solders used as bonding materials in the past is low, so sometimes sufficient strength cannot be obtained. Therefore, a metal bonding material with a higher melting point and a lower bonding temperature are required. Therefore, in order to study the applicability of the oxide-containing copper particles of the embodiment of the present invention as a bonding material, the bonding strength was investigated.
[0128] Copper particles prepared in the same manner as in the case of Samples No. 1 and 2 were added to a dispersion medium and dispersed using a high-pressure wet micronizer (STAR BURST mini (manufactured by SUGINO MACHINE). It should be noted that triethanolamine was used as a dispersion medium, and the content of the above copper particles was set to 90% by mass. In addition, the ejection pressure during dispersion was set to 150 MPa, and the ejected dispersion was dispersed while being cooled in an ice bath at 0° C., and this was repeated five times (i.e., the number of passes was set to five times). After the dispersion was completed, copper particles containing oxides dispersed in triethanolamine and coated with hexanoic acid (Sample No. 3) were obtained. For Sample No. 3, an XRD spectrum was obtained in the same manner as in the case of Samples No. 1 and 2, and Cu, Cu 64 O and Cu2O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is Cu: 98.8 mass%, Cu64 O: 1.2 mass %, Cu2O was not detected.
[0129] The adhesive strength of the sample No. 3 as a bonding material was examined.
[0130] First, using the oxide-containing copper microparticles of Sample No. 3, the adhesive strength when the test pieces were joined without applying pressure was examined in the following manner.
[0131] Copper cylindrical test piece 1 (φ5mm, height 5mm) and copper cylindrical test piece 2 (φ12mm, height 5mm) were prepared, and the surfaces of the respective flat parts were mirror-polished (alumina with a particle size of #4000 and a particle size of 0.5μm were used as abrasives, respectively). After polishing, copper cylindrical test piece 1 and copper cylindrical test piece 2 were cleaned with dilute hydrochloric acid. After cleaning, the oxide-containing copper particles of sample No. 3 were applied to one side of the flat part of copper cylindrical test piece 2. It should be noted that when applying, a metal mask with a circular opening (φ12mm, thickness 0.15mm, opening: φ5mm) was used, and the coating was performed only on the center of the flat part. One side of the flat part of copper cylindrical test piece 1 was made to fit closely with the coated surface (φ5mm), and a load of 160g was further applied and maintained for 30 seconds. After that, the copper cylindrical test piece 1 and the copper cylindrical test piece 2 were placed in a heating furnace under an inert gas atmosphere using a 100 mL / min N2 flow and heated. The temperature (and pressure) during heating are shown in the graph. Figure 7 .Depend on Figure 7 It can be seen that the heating temperature is 200° C. or lower.
[0132] As described above, the copper cylindrical test piece 1 and the copper cylindrical test piece 2 were joined together without applying pressure using the oxide-containing copper fine particles of Sample No. 3.
[0133] Using the test pieces bonded as above, the bonding strength was measured. Figure 8 A schematic diagram for explaining the method for measuring the bonding strength is shown in FIG. Figure 8 As shown, the copper cylindrical test piece 1 is clamped by a clamp 3, and the maximum load (MPa) applied when the copper cylindrical test piece 2 is moved in the direction of the dotted arrow at 1 mm / min is evaluated as the bonding strength. Fig. 9 The results of the bonding strength measurements are shown in FIG. Figure 8 The movement in the direction of the dotted arrow and the detection of the load during the bonding strength measurement were performed using an automatic servo vertical testing machine (JSV-H1000, manufactured by Nippon Testing Systems Co., Ltd.) and a handheld digital dynamometer (HF-100, manufactured by Nippon Testing Systems Co., Ltd.). Fig. 9When the copper cylindrical test piece 1 and the copper cylindrical test piece 2 were bonded together without applying pressure using the oxide-containing copper microparticles of sample No. 3, the bonding strength was 17.0 MPa.
[0134] The bonding surfaces (fracture surfaces) of the copper cylindrical test pieces 1 and 2 after the above-mentioned bonding strength measurement were observed using an optical microscope (VHX-7000, manufactured by KEYENCE CORPORATION). Fig.10 The optical microscope image of the fracture surface of the copper cylindrical test piece 1 is shown in Fig.11 An optical microscope image of the fracture surface of the copper cylindrical test piece 2 is shown in FIG. Fig.10 and Fig.11 Compared with the copper cylinder test piece 1, a large amount of sintered bodies of copper particles containing oxides of sample No. 3 remain in the copper cylinder test piece 2. Furthermore, the fracture surface of the copper cylinder test piece 2 was observed using FE-SEM (JSM-6701F, manufactured by JEOL Ltd.). Fig.12 FIG. 2 shows a FE-SEM image of the fracture surface of the copper cylindrical test piece 2. Fig.12 As shown, Figure 6 Similarly, the copper particles containing oxides of sample No. 3 were well necked, and a good sintering state was confirmed. Fig.12 The sintered body of the copper fine particles containing the oxide shown above exhibits sufficient conductivity.
[0135] Next, using the oxide-containing copper microparticles of Sample No. 3, the adhesive strength when the test pieces were press-bonded was examined in the following manner.
[0136] In the same manner as above, the oxide-containing copper particles of sample No. 3 are coated on the copper cylindrical test piece 2. One side of the flat portion of the copper cylindrical test piece 1 is brought into close contact with the coated surface (φ5 mm), and a load of 5 kg is further applied and maintained for 10 seconds. Thereafter, the copper cylindrical test pieces 1 and 2 are placed in a heating furnace under an inert gas atmosphere using a 100 mL / min N2 flow, and are heated while a load is applied to the flat portion of the test piece. The temperature and pressure measurement lines during heating are shown in FIG. Fig.13 .Depend on Fig.13 It can be seen that the heating temperature is 200° C. or lower.
[0137] Using the test pieces bonded as above, the bonding strength was measured. Figure 8 As shown in FIG. 1 , the copper cylindrical test piece 1 was clamped by a clamp 3, and the maximum load (MPa) applied when the copper cylindrical test piece 2 was moved in the direction of the dotted arrow at 1 mm / min was evaluated as the bonding strength. The bonding strength measurement results are shown in FIG. Fig.14 It should be noted that a small tabletop tester (EZ-X, manufactured by Shimadzu Corporation) was used for the test. Figure 8The movement in the direction of the dotted arrow and the load detection during the bonding strength measurement. Fig.14 When the copper cylindrical test piece 1 and the copper cylindrical test piece 2 were press-bonded using the oxide-containing copper microparticles of sample No. 3, the bonding strength was 63.9 MPa.
[0138] The bonding surfaces (fracture surfaces) of the copper cylindrical test pieces 1 and 2 after the above-mentioned bonding strength measurement were observed using an optical microscope (VHX-7000, manufactured by KEYENCE CORPORATION). Fig.15 The optical microscope image of the fracture surface of the copper cylindrical test piece 1 is shown in Fig.16 An optical microscope image of the fracture surface of the copper cylindrical test piece 2 is shown in FIG. Fig.15 and Fig.16 The sintered body of sample No. 3 remained in both copper cylindrical test piece 1 and copper cylindrical test piece 2. Furthermore, the fracture surface of copper cylindrical test piece 2 was observed using FE-SEM (JSM-6701F, manufactured by JEOL Ltd.). Fig.17 The FE-SEM image of the fracture surface of the copper cylindrical test piece 2 is shown in FIG. Fig.17 The copper particles containing oxides of sample No. 3 were well necked, confirming a good sintering state. Fig.17 The sintered body of the copper fine particles containing the oxide shown above exhibits sufficient conductivity.
[0139] This application claims priority based on Japanese Patent Application No. 2020-144680, filed on August 28, 2020. Japanese Patent Application No. 2020-144680 is incorporated herein by reference.
[0140] Industrial Applicability
[0141] The oxide-containing copper particles of the embodiment of the present invention do not require two-stage heating and additional copper materials. By heating once at 200°C or below under normal pressure (or pressure above it), a sintered body showing sufficient conductivity can be obtained. Therefore, in addition to circuit forming materials for printed circuit boards (especially flexible circuit boards) and other micro wiring materials, it can also be used as a die bonding material for power semiconductors as a heat conduction purpose. In addition, it can also be used as an antistatic material, an electromagnetic wave shielding material, and an infrared shielding material.
Claims
1. An oxide-containing copper particle comprising Cu 64 O and Cu2O as required, and coated with carboxylic acids, wherein Cu 64 O relative to Cu, Cu 64 The mass ratio of the total mass of O and Cu2O is 0.5 to 2.0 mass%, Cu2O is relatively 64 The mass ratio of the total mass of O and Cu2O is greater than 0 mass% and less than 0.5 mass%.
2. A method for producing oxide-containing copper particles, which is the method for producing oxide-containing copper particles according to claim 1, the method comprising: A process for preparing copper particles; A step of coating the copper particles with carboxylic acids; as well as The copper fine particles coated with the carboxylic acid are added to a dispersion medium and dispersed using a bead mill or a high-pressure wet micronizing device. The dispersing step is performed under an inert gas atmosphere.
3. The manufacturing method according to claim 2, wherein: The rotation speed of the agitator of the bead mill is 1000 rpm or more and less than 3000 rpm.
4. A method for producing a sintered copper particle body, comprising: A step of heating the oxide-containing copper fine particles according to claim 1 to 100° C. to 200° C. in an inert gas atmosphere.
5. The manufacturing method according to claim 4, wherein: The inert gas includes N2.
6. The manufacturing method according to claim 5, wherein: The inert gas is mixed with less than 4 volume % of H2.
Citation Information
Patent Citations
Method for manufacturing copper fine particle sintered body and conductive substrate
JP2015214722A
Method of producing copper complex and composition for forming conductive film containing the same
JP2017001978A
Method of assisting healthcare professionals in interpretation of genetic information, information management system, and integrated data management device
JP2020144680A
Low-temperature-sinterable copper particle and method for manufacturing sintered compact using same
WO2019106739A1